Personality traits and basic psychological need satisfaction: Their relationship to apprentices' life satisfaction and their satisfaction with vocational education and training. (2019) - Volodina, Anna; Lindner, Christoph; Retelsdorf, Jan
Highlights: Apprentices distinguished between their need satisfaction in different contexts. Personality traits mainly predicted life satisfaction. Basic psychological need satisfaction mainly predicted context-specific outcome. Basic psychological need satisfaction predicted outcomes above personality traits. Abstract: The present study investigated the role that personality traits and basic psychological need satisfaction (BPNS) play in apprentices' satisfaction with vocational education and training (VET) and life satisfaction in two different contexts (the company and the vocational school). Drawing on a German sample of N  = 2, 477 apprentices in their first year of VET, BPNS in the two contexts could be differentiated between. Furthermore, the way in which BPNS and personality traits were related to VET satisfaction and life satisfaction varied between the two contexts; personality traits mainly predicted life satisfaction, whereas BPNS at the company mainly predicted VET satisfaction. Our results indicate that personality traits are particularly relevant for general outcomes, whereas BPNS is more related to context-specific outcomes.